Meningkatkan Nilai Kebangsaan Siswa Melalui Program Sekolah Aiwiyata di SDN 4 Made Lamongan - Durrotun Nafisah; Yayuk Chayatun Machsunah (IKIP PGRI Bojonegoro, 2023)
Abstract: One form of citizens' love for their homeland is protecting and caring for the natural environment. The national values of loving the motherland, caring for the environment are carried out from an early age through learning at school. School education is a place to create students to have attitudes and skills in preventing damage to the surrounding environment. The Adiwiyata school program which is integrated into Pkn subjects is expected to be able to increase students' national values. Information sources for school principals, teachers, employees and students. Data was collected through observation, in-depth interviews and documentation. The main research instrument itself. Data analysis techniques by means of data reduction, data presentation and drawing conclusions. The results of the study show that the Adiwiyata school program can increase national values. Praxis carried out to foster national values include 1) school policies related to caring for the environment; 2) development of an environment-based curriculum; 3) integration of the environment in all subjects, especially the Pancasila and Citizenship Education subjects; 4) development of facilities and infrastructure related to the environment. The national values that are formed include the value of devotion to God Almighty; unity, solidarity, mutual cooperation, tolerance, humanity, justice and the preservation of environmental functions and natural resources. Keyword: National Values, Adiwiyata School Abstrak: Salah satu bentuk cinta tanah air warga negara adalah menjaga dan melestarikan lingkungan alam sekitar. Nilai-nilai kebangsaan cinta tanah air, peduli lingkungan dilakukan sejak dini melalui pembelajaran di sekolah. Pendidikan sekolah menjadi tempat untuk menciptakan peserta didik agar memiliki sikap dan ketrampilan dalam mencegah kerusakan lingkungan sekitar. Program sekolah adiwiyata yang diintegrasikan pada mata pelajaran Pkn diharapkan mampu meningkatkan nilai-nilai kebangsaan siswa. Sumber informasi kepala sekolah, guru, karyawan dan siswa. Data dikumpulkan melalui observasi, wawancara secara mendalam dan dokumentasi. Instrumen utama peneliti sendiri. Teknik analisis data dengan cara reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa program sekolah adiwiyata dapat meningkatkan nilai kebangsaan. Praksis yang dilakukan untuk menumbuhkan nilai-nilai kebangsaan antara lain 1) kebijakan sekolah terkait peduli lingkungan; 2) pengembangan kurikulum berbasis lingkungan; 3) integrasi tentang lingkungan di semua mata pelajaran khususnya mata pelanjaran Pendidikan Pancasila dan Kewarganegaraan; 4) pengembangan sarana dan prasarana terkait lingkungan. Nilai kebangsaan yang terbentuk antara lain nilai ketaqwaan kepada Tuhan YME; persatuan, kesetiakawanan, gotong royong, toleransi, kemanusiaan, keadilan serta kelestarian fungsi lingkungan hidup dan sumberdaya alam. Kata kunci: Nilai Kebangsaan, Sekolah Adiwiyata